The Effect of Uncaria Gambier Roxb Extract on Levels of F2-Isoprostanes in the Submaximal Exercise - Syahrastani; Yuniarti , Elsa; Hilda Putri, Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Athletes always do strenuous physical exercises to prepare themselves to face a championship or a match in a short time. The exercise that is fatiguing will increase the formation of free radicals that can damage the cell membrane with the peroxidation process of lipids, so F2-isoprostane will form. This process can be prevented by giving antioxidants from Uncaria gambier Roxbextract that contains a high level of catechins. This study is aimed at determining the effect of Uncaria gambier Roxburgh extract on levels of F2-isoprostanes in education center and sport training students in West Sumatera who perform submaximal exercises. This study was experimented with as a pre-test and post-test group design for 17 students of football in PPLP West Sumatera. 500 mg of Uncaria gambier Roxburgh extract is given 2 hours before submaximal exercises. The method to examine the F2-isoprostanes is ELISA. Statistical analysis was paired samples t-test, and the results obtained were statistically significant when p < 0.05. There is a different effect of F2-isoprostanes levels before and after the administration of Uncaria gambier Roxburgh extract: 48.8+16.9 pg/ml vs 35.3+15.1 pg/ml, p<0.001. Giving Uncaria gambier Roxburgh extract may affect the levels of F2-isoprostanes in those who perform submaximal exercise with significance.